Aspectos Psicológicos en niños con labio leporino y/o Paladar hendido: un breve comentario sobre algunos hallazgos relevantes para los equipos de salud - Marcos Roberto Tovani Palone (Revista de Salud Pública)
Individuals with these anomalies have anatomical deformities that commonly involve the lip, alveolar ridge and palate.Consequently, both aesthetics and function are impairedin the vast majority of cases(1). In view of this, the treatment of people with CL/P often requires multiple surgeries and other therapies throughout childhood, adolescence and adulthood(4-6). In addition, these craniofacial malformations can influence, among other things, the self-perception and social functioning of affected individuals, even after surgical repair(7).Therefore, multidisciplinary care isnecessary for successful treatment of these individuals(1,8).